According to the zero power rule of integer exponents, any non-zero number raised to the power of zero is equal to 1.
Therefore,
\[ 63^0 = 1. \]
63^0=___
7 answers
According to the zero power rule of integer exponents, any non-zero number raised to the power of zero is equal to 1.
Therefore,
\[ 63^0 = 1. \]
To solve the expression \( 2.3 + (-1.478)^0 \), we apply the zero power rule. According to this rule, any non-zero number raised to the power of zero equals 1.
Since \(-1.478\) is not zero, we have:
\[ (-1.478)^0 = 1 \]
Now, we can substitute this back into the expression:
\[ 2.3 + (-1.478)^0 = 2.3 + 1 \]
Adding these together gives:
\[ 2.3 + 1 = 3.3 \]
Therefore,
\[ 2.3 + (-1.478)^0 = 3.3 \]
To solve the expression \(-4^0 \cdot 15\), we first apply the zero power rule.
According to the rule, any non-zero number raised to the power of zero is equal to 1.
Thus:
\[ -4^0 = 1 \]
Now substituting this into the expression:
\[ -4^0 \cdot 15 = 1 \cdot 15 = 15 \]
Therefore,
\[ -4^0 \cdot 15 = 15. \]
To solve the expression \(-4^0 \times 15\), we first need to evaluate \(-4^0\).
According to the zero power rule, any non-zero number raised to the power of zero is equal to 1. Thus:
\[ -4^0 = 1 \]
Now we can substitute this value back into the expression:
\[ -4^0 \times 15 = 1 \times 15 \]
This simplifies to:
\[ 1 \times 15 = 15 \]
Therefore:
\[ -4^0 \times 15 = 15. \]